2023
DOI: 10.1097/prs.0000000000010470
|View full text |Cite
|
Sign up to set email alerts
|

Novel Port Placement in Robotic-assisted DIEP Flap Harvest Improves Visibility and Bilateral DIEP Access: Early Controlled Cohort Study

Abstract: Summary: To minimize donor-site damage, robot-assisted (RA) deep inferior epigastric perforator (DIEP) flap harvest has been suggested. Current robotic approaches favor port placement, which either does not allow a bilateral DIEP flap harvest through the same ports or necessitates additional scars. In this article, the authors propose a modification of port configuration. In a retrospective controlled cohort study, RA-DIEP and conventional DIEP surgery were compared. The perforator and pedicle were visualized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…9 10 53 Tsai et al found a significantly reduced incision length (2.67 ± 1.13 cm) of the anterior rectus sheath in patients undergoing robotic DIEP reconstruction when compared to conventional DIEP patients (8.14 ± 1.69). 49 Additional studies describe similar findings, reporting fascial incisions measuring 1.5 to 4.3 cm. 9 10 46 49…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…9 10 53 Tsai et al found a significantly reduced incision length (2.67 ± 1.13 cm) of the anterior rectus sheath in patients undergoing robotic DIEP reconstruction when compared to conventional DIEP patients (8.14 ± 1.69). 49 Additional studies describe similar findings, reporting fascial incisions measuring 1.5 to 4.3 cm. 9 10 46 49…”
Section: Discussionmentioning
confidence: 65%
“…49 Additional studies describe similar findings, reporting fascial incisions measuring 1.5 to 4.3 cm. 9 10 46 49…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations